Entrapment of the popliteal artery and its surgical management in a 20-year period - Hölting, Thomas; Schürmann, Guido; Allenberg, Jens-Rainer (The British journal of surgery, 1997)
This study was a retrospective review of 19 patients with popliteal artery entrapment syndrome (PAES) treated in a 20-year interval.The Heidelberg classification of PAES was used, which differentiates three categories of entrapment: in type I the popliteal artery has an atypical course, in type II the muscular insertion is atypical, and in type III both conditions are present. Besides decompression of the popliteal artery the commonest operative reconstruction used was resection of the atherosclerotic part of the artery and autologous vein interposition grafting (n = 12). Local thromboendarterectomy was done in seven cases, six with a vein patch angioplasty repair.Follow-up ranged from 6 months to 20 years (mean 9·5 years). There was no limb loss. The rate of complications was lowest after primary venous interposition (two of 12) compared with five of 11 when venous interposition was not used (P<0·01).Autologous saphenous vein interposition grafting seems to be the best treatment for PAES.